Pemeriksaan Kesehatan Gratis Sebagai Upaya Peningkatan Kesehatan Masyarakat Di Kelurahan Laikang - Adriani, Fitri; Ningsi Angraeni; Arfiani; Lilis Suryani; Samila (JCS, 2025)
Regular health checks are an important step in early detection and prevention of diseases, especially Non-Communicable Diseases (NCDs) such as hypertension, diabetes mellitus, high cholesterol, and gout. Lack of public awareness of the importance of regular health checks is a challenge in controlling these diseases. This community service activity was carried out in Laikang Village, Biringkanaya District, through free health education and examinations as a form of contribution to increasing public awareness and health status. The activity methods included education on blood pressure, blood sugar, uric acid, and cholesterol as well as direct examinations of 55 participants consisting of pregnant women and the elderly. The results of the activity showed high community enthusiasm and increased understanding of the importance of routine health checks. This activity also succeeded in identifying several cases of NCDs that had not been previously diagnosed. Limited equipment and medical personnel were challenges in implementation, but overall this program showed effectiveness as a means of promotion and prevention in improving public health. In the future, it is hoped that similar activities can be carried out periodically and sustainably.